The Effect of Maternal Mirroring Behavior on Infants' Early Social Bidding During the Still‐Face Task. (12th October 2017) - Bigelow, Ann E.; Power, Michelle; Bulmer, Maria; Gerrior, Katlyn
Abstract : Maternal mirroring behavior, which is a particularly salient form of maternal responsiveness, was investigated as a predictor of infants' social bids in the Still‐Face Task. Mother–infant dyads engaged in the Still‐Face Task when infants were 5 months, on the cusp of the active emergence of social bidding during the still‐face phase of the task. Maternal mirroring of infants' behavior during the interactive phases of the task was a primary predictor of infants' social bids in the still‐face phase. When infants were divided into those who experienced higher maternal mirroring (maternal mirroring above the mean of the sample) and infants who experienced lower maternal mirroring (maternal mirroring at or below the mean), infants with higher maternal mirroring showed increases in nondistress vocalizations during the still‐face phase, indicative of social bidding, whereas the infants with lower maternal mirroring showed little change in nondistress vocalizations across the phases. Maternal mirroring allows infants to readily notice the relation between their own behaviors and those of their mothers, which may enhance infants' early understanding that they can be active agents in instigating social interactions, as demonstrated by social bidding.